Modelling the Potential Public Health Impact of Different COVID-19 Vaccination Strategies with an Adapted Vaccine in Singapore - Karan Thakkar; Julia Spinardi; Moe H. Kyaw; Jingyan Yang; Carlos Fernando Mendoza; Egemen Ozbilgili; Bulent Taysi; Josie Dodd; Ben Yarnoff; Helen M Oh (Expert Review of Vaccines)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 has been a dynamically changing virus, requiring the development of adapted vaccines. This study estimated the potential public health impact alternative vaccination strategies for COVID-19 in Singapore.Research Design and Methods The outcomes of alternative vaccination strategies with a future adapted vaccine were estimated using a combined Markov decision tree model. The population was stratified by high- and standard-risk. Using age-specific inputs informed by local surveillance data and published sources, the model estimated health (case numbers, hospitalizations, and deaths) and economic (medical costs and productivity losses) outcomes in different age and risk subpopulations.Results Booster vaccination in only the elderly and high-risk subpopulation was estimated to avert 278,614 cases 21,558 hospitalizations, 239 deaths, Singapore dollars (SGD) 277 million in direct medical costs, and SGD 684 million in indirect medical costs. These benefits increased as vaccination was expanded to other subpopulations. Increasing the booster vaccination coverage to 75% of the standard-risk population averted more deaths (3%), hospitalizations (29%), infections (145%), direct costs (90%), and indirect costs (192%) compared to the base case.Conclusions Broader vaccination strategies using an adapted booster vaccine could have substantial public health and economic impact in Singapore.